2013
DOI: 10.1159/000345375
|View full text |Cite
|
Sign up to set email alerts
|

Association of Nesfatin-1 and Fat Mass in Cystic Fibrosis

Abstract: Background: The mechanisms of fat mass (FM) loss in cystic fibrosis (CF) are poorly understood but could represent complex pathways involving dysregulation of appetite-modulating peptides and an amplified inflammatory response. Nesfatin-1 is a newly described peptide that decreases food intake and FM but has not been studied in CF. Objectives: We hypothesized that changes in the appetite-suppressing hormone nesfatin-1 would be physiological, and levels would be lower in advanced CF patients with lower FM compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In 2013, Cohen et al observed increased plasma nesfatin-1 concentrations in CF patients with more advanced disease and lower fat mass; this was surprising because nesfatin-1 is an anorexigenic factor. This effect was not found to be related to IL-6 and TNF-α [22].…”
Section: Discussionmentioning
confidence: 62%
“…In 2013, Cohen et al observed increased plasma nesfatin-1 concentrations in CF patients with more advanced disease and lower fat mass; this was surprising because nesfatin-1 is an anorexigenic factor. This effect was not found to be related to IL-6 and TNF-α [22].…”
Section: Discussionmentioning
confidence: 62%
“…Our patients are outpatients, and their mobility may explain the relative protection of muscle masses while decreasing fat masses. In a study evaluating nesfatin-1 levels in patients with cystic fibrosis (12), high nesfatin-1 levels with low fat mass were detected in patients with severe cystic fibrosis. In our study, there was no significant change in nesfatin-1 values with decreased fat mass in severe COPD patients.…”
Section: Discussionmentioning
confidence: 99%
“…A significant negative correlation between NUCB2/Nesfatin-1 levels and FM was found only in the severe CF group (r= -0.7, p=0.003). They also further suggested that NUCB2/ Nesfatin-1 exerted its effects independently of TNF-α or IL-6 [17]. Thus, inconsistent results have been obtained with respect to BMI and NUCB2/Nesfatin-1 expression, and the different ranges of selected BMI and the distinct detection sensitivity of NUCB2/Nesfatin-1.…”
Section: Genomics and Protein Structure Of Nucb2/nesfatin-1mentioning
confidence: 99%